Utilization Of Organic Waste As Feed On The Cultivation Of Tilapia (Oreochromis Niloticus) With Biofloc System In Sitirejo Village - winda firdayanti (Journal of Innovation and Applied Technology, 2018)
One of the main commodities of aquaculture fishery in Indonesia is tilapia (Oreochromis niloticus). One of the competitive constraints of the farmers in the field is the price of feed is quite expensive, so 60-70% of the production costs used for feed. The purpose of this activity is to utilize the organic waste as fish feed in the TPST (Integrated Waste Management Site) in Sitirejo Village to be processed as fish feed. The method used in this activity is Participatory Rural Appraisal (PRA) which involves the community in the activity. Implementation of this activity includes socialization, training, monitoring and evaluation. Organic waste materials such as leek, celery, mustard, cabbage, sprout, corncobs, grated coconut pulp, fruit like melon, papaya, pineapple, apple, bone and fish head. Organic feed was applied to 3 tilapia ponds with a diameter of 2 meters with a weight of 400 fish per pond. Tilapia seed used is measuring 10-12 cm. An organic feed is given twice daily with a dose of 5% of the fish weight. After ± 75 days of maintenance, the yield of 223 kg of tilapia produced from 3 ponds of biofloc.. The application of organic feed is able to reduce production costs up to 56.25% of the use of factory feed at a cost of Rp 4,350,000 to 1,902,850 when applied feed from organic waste.